THE EFFECT OF THE PROCESSING PROCESS (BLANCHING) ON THE MICROBIOLOGICAL AND ORGANOLEPTIC QUALITY OF DRIED ANCHOVIES (Stolephorus sp.) - Rahmawati Idrus; Mutemainna Karim (Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
anchovies (Stolephorus sp.) Blanching is a heat process that uses hot water or steam, and this heating generally takes place at a temperature of 85°C. This study aims to determine the effect of blanching on the processing process of dried anchovies on the content of microbiological values (total plate number), moisture content, and organoleptics of dried anchovies (Stolephorus sp) in Barru district. This research will be carried out in April 2025. This test was carried out at the Microbiology and Biochemistry Laboratory of the Pangkajene and Islands State Agricultural Polytechnic and organoleptic testing was carried out at the Barru Regency Fisheries Office. This research method uses a descriptive method with test parameters Total plate number (ALT), moisture content, organoleptic (appearance, smell, taste, texture, mold) The test was carried out with two treatments, namely dried anchovies that were blanching (A) and dried anchovies without blanching (B) and 3 repetitions with the product storage period in week 1, week 2, and week 3. The results showed that the blanching method in the dried anchovy processing process had a real effect on the microbiological and organoleptic quality, where the ALT test showed that the number of microbes in the blanching fish samples was lower than the samples without blanching. The number of microbes in sample A was within safe limits for 3 storage times while in sample B it had passed the threshold in the third week of storage, which was 140,000 colonies/gram. The growth in the number of microbes in each storage period was very drastic compared to sample A. The results of organoleptic tests showed that dried anchovies that went through the blanching method had a better value than anchovies without blanching, namely the average value of sample A 8.35 looked clean, while sample B 6.3 appeared intact but not clean. The average odor in sample A was 8.1 without additional odor while sample B 6.3 had little additional odor. In the specification of the taste of sample value A 6.9 while sample B 5.5 has a slight taste of tamabahn and in the texture test the value of sample A 8.35 is compact while sample B 6.0 looks solid and dry